TAR syndrome: Clinical and molecular characterization of a cohort of 26 patients and description of novel noncoding variants of RBM8A. Issue 7 (6th April 2020) - Boussion, Simon; Escande, Fabienne; Jourdain, Anne‐Sophie; Smol, Thomas; Brunelle, Perrine; Duhamel, Céline; Alembik, Yves; Attié‐Bitach, Tania; Baujat, Geneviève; Bazin, Anne; Bonnière, Maryse; Carassou, Philippe; et al.
Abstract: Thrombocytopenia‐absent radius (TAR) syndrome is characterized by radial defect and neonatal thrombocytopenia. It is caused by biallelic variants of RBM8A gene (1q21.1) with the association of a null allele and a hypomorphic noncoding variant. RBM8A encodes Y14, a core protein of the exon junction complex involved in messenger RNA maturation. To date, only two hypomorphic variants have been identified. We report on a cohort of 26 patients affected with TAR syndrome and carrying biallelic variants in RBM8A . Half patients carried a 1q21.1 deletion and one of the two known hypomorphic variants. Four novel noncoding variants of RBM8A were identified in the remaining patients. We developed experimental models enabling their functional characterization in vitro. Two variants, located respectively in the 5′‐untranslated region (5′‐UTR) and 3′‐UTR regions, are responsible for a diminished expression whereas two intronic variants alter splicing. Our results bring new insights into the molecular knowledge of TAR syndrome and enabled us to propose genetic counseling for patients' families.